Uji Eksperimental Konsumsi Bahan Bakar Mesin Berbahan Bakar Biodiesel Minyak Kelapa Hasil Metode Kering - Padang, Yesung Allo (Universitas Mataram, 2011)
Experimental testing using coconut oil produced by dry method on engine has been conducted in the Laboratory of Energy Conversion, Mechanical Engineering, Mataram University. The purpose was to evaluate the effect of using this coconut oil on the engine performance. The oil was mixed with diesel oil in order to obtain biodiesel. There were four combinations of ratio diesel oil to coconut oil; namely 100% : 0% (mkp0%), 90%:10% (mkp10%), 80%:20% (mkp20%) and 70%:30% (mkp30%.). Mitsubishi L300 diesel engine was used in this experiment by variating engine speed 1000 rpm, 1050 rpm and 1100 rpm with torgue load at 1 kg. At engine speed of 1200 rpm the loads were varied as 1 kg, 1.5 kg and 2 kg. The result shows that by increasing the number of coconut oil in the mixture will reduce engine fuel consumption. Fuel consumption of the mixture will be better compare to the fuel consumption of pure diesel oil. Specific fuel consumption efective (SFCe) of coconut oil-diesel mixture at mkp 10%, 20% and 30% are lower than of pure diesel oil. The reduced SFCe are 1.45 %, 1.71% and 3.57 % at effective power 0.838 PS, 1.98%, 4.31% and 4.31% at effective power 1.257 PS and 1.22%, 3.92% and 7.12% at effective power 1.676 PS. By varying the engine speed, the result also shows that SFCe of the mixture is also lower than SFCe of pure diesel oil.